Peranan UPTD Dinas Sosial Provsu Dalam Peningkatan Kesejahteraan Lanjut Usia (LANSIA) Terlantar Di Kota Binjai - Frastito, Frastito; Suharyanto, Agung; Deliana, Marlina (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2025)
This study aims to examine the role of the Regional Technical Implementation Unit (UPTD) of the North Sumatra Provincial Social Service (Provsu) in improving the welfare of the abandoned elderly in Binjai City. The abandoned elderly are a vulnerable group that needs special attention because they do not have family support, housing, or a fixed income. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and documentation. The informants consisted of UPTD officers, elderly service recipients, and community leaders. The results of the study show that the UPTD of the Provsu Social Service has carried out various programs such as the provision of social institutions, basic needs assistance, health services, social and psychological coaching, and empowerment of the elderly. This program is generally considered effective in improving the quality of life of the elderly, but it is still faced with many obstacles such as budget limitations, inadequate facilities, and low public awareness. This study recommends increasing budget allocation, strengthening cross-sector cooperation, utilizing information technology, and educational campaigns as strategic steps to increase program effectiveness and create a more sustainable social protection system for the elderly.